Simultaneous Two‐Point Study of the Martian Bow Shock Affected by an Interplanetary Coronal Mass Ejection: Tianwen‐1 and MAVEN Observations - Ming Wang; Jiaqi Zhang; Jianyong Lu; Lianghai Xie; Fuhao Qiao; Qi Xu; Jinyu Li; Guanchun Wei; Baohang Qu; Lei Li (Geophysical Research Letters)
Abstract The Martian bow shock (BS) plays a significant role in the Martian plasma environment. Based on observations from Tianwen‐1 and MAVEN, we first report two cases of simultaneous two‐point crossings of the Martian BS affected by an interplanetary coronal mass ejection (ICME) event. The findings suggest that high solar wind dynamic pressure, Pd, and interplanetary magnetic field intensity, Bt, within an ICME event have opposite effects on the Martian BS. A high Pd causes the BS to move closer to the planet, while a strong Bt makes it move outward. The precise location of the BS depends on which factor dominates each time under specific ICME conditions. The two examined cases indicate that the Martian BS tends to move outward under an ICME event with a generally large IMF magnitude. The Wang, Xie, et al. (2020, https://doi.org/10.3847/1538‐4357/abbc04) model can accurately predict the location of the Martian BS under the examined ICME event.